Nutrition and soil erosion the influence of soil erosion on food and nutritional intake of rice farming communities in rainfed areas - Dela Cruz, James D. (2016)
Rice, the world's number one source of food, is also the top source of livelihood of the agriculture sector in the Philippines. However, due to soil erosion, the declining rice productivity is threatened to become worse. This study determined the effect of soil erosion on the productivity of rainfed rice farms in Compostela Valley. After being determined using GIS, two groups of erosion levels were analyzed in this study, the moderate erosion and without erosion. An OLS production function model was used to determine the effect of erosion on the inputs of production and how each of these inputs affects the production function were determined. Household expenditure patterns and nutrient intakes among children in the farm households were analyzed and nutrient conversion used was from Philippine Dietary Intakes Table. Based on the results, soil erosion level has a negative effect on farm productivity and nutrient intake level of children. Nutrient deficiency is also prevalent among children in the rainfed rice farms having inadequate nutrient levels in contrast to the prescribed energy and nutrient intake. Several programs and courses of actions to combat the effect of soil erosion is presented in this study.